Implementing Cisco Unified Communications Manager, Part 1 (CIPT1) Foundation Learning Guide : (CCNP Voice CIPT1 642-447), Second Edition - Finke, Joshua (Cisco Press, 2011)
This is Cisco's authorized, self-paced, foundation learning tool for the new CIPT1 8.0 exam (Implementing Cisco Unified Communications Manager, Part 1), required for the new CCNP Voice certification. It offers yuou a complete, engineering-level understanding of planning, deploying, and managing single-site IP Telephony environments based on Cisco Unified Communications Manager (CUCM) 8.x. As an Authorized Self-Study Guide, this book fully reflects the content of the newest versions of the Cisco CIPT1 course. Each chapter ends with 20 questions designed to help you assess your understanding as you prepare for the exam. Older material has been removed from this edition, and three new chapters have been added to cover: " Cisco Unified Communications Manager Phone Services " Implementing Cisco Unified Manager Assistant " Implementing Cisco Unified Mobility.